Design and Validation of a Device for Mitigating Fluid Microgravity Effects in Biological Research in Canister Spaceflight Hardware - Nicholson, Wayne L.; Fajardo-Cavazos, Patricia; Turner, Caleb; Currie, Taylor M.; Gregory, Geoffrey; Jurca, Titel; Weislogel, Mark (Frontiers in Space Technologies, 2021)
The major factor influencing the behavior of microbes growing in liquids in space is microgravity. We recently measured the transcriptomic response of the Gram-positive bacterium Bacillus subtilis to the microgravity environment inside the International Space Station (ISS) in spaceflight hardware called Biological Research in Canisters-Petri Dish Fixation Units (BRIC-PDFUs). In two separate experiments in the ISS, dubbed BRIC-21 and BRIC-23, we grew multiple replicates of the same B. subtilis strain in the same hardware, growth medium, and temperature with matching ground control samples (npj Micrograv. 5:1.2019, doi: 10.1038/s41526-018-0061-0). In both experiments we observed similar responses of the transcriptome to spaceflight. However, we also noted that the liquid cultures assumed a different configuration in microgravity (a toroidal shape) compared with the ground control samples (a flat disc shape), leading us to question whether the transcriptome differences we observed were a direct result of microgravity, or a secondary result of the different liquid geometries of the samples affecting, for example, oxygen availability. To mitigate the influence of microgravity on liquid geometry in BRIC canisters, we have designed an insert to replace the standard 60-mm Petri dish in BRIC-PDFU or BRIC-LED sample compartments. In this design, liquid cultures are expected to assume a more disk-like configuration regardless of gravity or its absence. We have: (i) constructed a prototype device by 3D printing; (ii) evaluated different starting materials, treatments, and coatings for their wettability (i.e., hydrophilicity) using contact angle measurements; (iii) confirmed that the device performs as designed by drop-tower testing and; (iv) performed material biocompatibility studies using liquid cultures of Bacillus subtilis and Staphylococcus aureus bacteria. Future microgravity testing of the device in the ISS is planned.